The American buffalo [videorecording (DVD)] - Duncan, Dayton; Coyote, Peter; Brannum, Julianna (PBS, 2023)
" ... America's national mammal, which sustained the lives of Native people for untold generations, being driven to the brink of extinction, before an unlikely collection of people rescues it from disappearing forever."--Container.